Increased motor cortex excitability in chronic complex regional pain syndrome - Vanhanen, Jukka; Nordberg, Janne; Paavola, Janika; Julkunen, Petro; Munoz, Miguel; Mäkelä, Jyrki P.; Vaalto, Selja; Kirveskari, Erika; Jääskeläinen, Satu (Elsevier BV, 2025)
Objective
To characterize corticospinal excitability and cortical motor representation in complex regional pain syndrome (CRPS) type I and type II, addressing inconsistencies in prior research regarding these mechanisms.
Methods
Fifty-nine CRPS patients (44 type I and 15 type II) underwent TMS and paired-pulse TMS examinations to assess resting motor threshold (RMT), motor evoked potential (MEP) amplitude and latency, short-interval intracortical inhibition (SICI), and intracortical facilitation (ICF) bilaterally, alongside cortical representation areas of the hands at M1 cortex. Results were compared with 23 healthy subjects.
Results
CRPS patients had lower RMT, higher MEP amplitudes, and lower ICF than healthy subjects. The SICI in CRPS patients showed no interhemispheric differences and did not differ from healthy subjects. MEP latency was shorter to the affected than to the unaffected hand in CRPS type II. Higher pain intensity correlated with higher degree of intracortical facilitation bilaterally, and with smaller motor representation area of the unaffected hand.
Conclusion
Findings of this study suggest increased motor cortical excitability in CRPS patients relative to healthy subjects, with no interhemispheric asymmetry of SICI or ICF observed in chronic CRPS.
​​​​​​​
Significance
These results provide a comprehensive view of intracortical inhibition, facilitation and corticospinal excitability in chronic CRPS.